Spatial and temporal determinants of golden sun moth Synemon plana distribution. (12th August 2014) - Kutt, A. S.; McKenzie, V. J.; Wills, T. J.; Retallick, R. W. R.; Dalton, K.; Kay, N.; Melero‐Blanca, E.
Abstract In this study we examined the spatial and temporal variation in a population of the critically endangered golden sun moth Synemon plana over four years in a conservation reserve in south‐eastern Australia. We found golden sun moth spatial distribution and abundance dramatically declined from a peak in extent and abundance from 2008–2009 to 2011–2012 due to a shift from drought to above average rainfall. Autoregressive correlative models indicated that a northerly aspect and landscape position were key predictors of abundance over time, and golden sun moth distribution shifted from wet to dry locations in the landscape. We conclude that: our data provide a counterpoint to conclusions that golden sun moth has been known to persist in very small areas and suggest that distribution can change quite markedly (from large connected populations to small patches) at a local scale, and this will be due to dispersal and survivorship; the variability in the data may have implications for adequate detection of the species over time, especially when populations have contracted and species have a naturally restricted activity and breeding period; and long‐term weather patterns and landscape configuration (aspect, wet or dry position) interact to significantly affect local distribution and abundance over time. This has implications for the species under global change; increased variability in rainfall, temperature, productivity and exotic pasture growth may all alter and interact to either reduce or enhance persistence of golden sun moth populations over time.